(untitled) (Journal of Student Affairs in Africa, 2021)
In 2014, through the University of the Free States (UFS) Institute for Reconciliation and Social Justice (IRSJ), three South African universities partnered to collaborate on the pilot phase of a research project focused on understanding whether the Arts could enable social cohesion, as the 2012 National Development Plan (2030) had promoted. The project, which had been conceptualised by one of the authors of this article in early 2014,1 followed both experience and observation of the challenges with regards thisconcept in the Arts, Culture and Heritage sectors of South Africa. Subsequent reflection and questioning of some of the related challenges, problematised the role that higher education had in societal transformation, and accordingly, in the conceptual development of social cohesion: Were universities creating appropriate conceptual frameworks and praxes required for the post-apartheid South African context?